A Contribution to the Shrubs and Woody Climbers of the Forests of Bankura District, West Bengal - Sanyal, M. N. (Indian Forester, 1973)
The paper presents the essential features of topography, soil, climate and forest-vegetation of the district of Bankura, West Bengal. It also deals with the enumeration of 52 angiospermic forest plants including woody climbers and shrubs belonging to 26 families. Flowering and fruiting times, place of collection etc. have also been mentioned.